2017
DOI: 10.1002/2017jd027070
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of light‐absorbing particles in snow across the Arctic, North America, and China: Effects on surface albedo

Abstract: Using field observations, we perform radiative transfer calculations on snowpacks in the Arctic, China, and North America to quantify the impact of light‐absorbing particles (LAPs) on snow albedo and its sensitivity to different factors. For new snow, the regional‐averaged albedo reductions caused by all LAPs in the Arctic, North America, and China are 0.009, 0.012, and 0.077, respectively, of which the albedo reductions caused by black carbon (BC) alone are 0.005, 0.005, and 0.031, corresponding to a positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
89
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(94 citation statements)
references
References 67 publications
(154 reference statements)
5
89
0
Order By: Relevance
“…However, even as the Arctic continues to warm at twice the rate of the global average, we find that the net regional climatic impact of trans-Arctic shipping emissions will likely be less warming. This is because in contrast to previous studies, increased BC emissions do not cause significant warming in our simulations relative to cloud radiative effects, in line with minor BC radiative forcing found in the Arctic from in situ measurements (0.06 W/m 2 ) and previous model simulations (0.51 W/m 2 ; Dang et al, 2017;Qian et al, 2014). Instead, aerosol direct effects are offset by reduced water vapor enabling increased shortwave downwelling and reduced surface albedo from BC is counteracted by substantial increases in cloud albedo.…”
Section: Discussionsupporting
confidence: 80%
“…However, even as the Arctic continues to warm at twice the rate of the global average, we find that the net regional climatic impact of trans-Arctic shipping emissions will likely be less warming. This is because in contrast to previous studies, increased BC emissions do not cause significant warming in our simulations relative to cloud radiative effects, in line with minor BC radiative forcing found in the Arctic from in situ measurements (0.06 W/m 2 ) and previous model simulations (0.51 W/m 2 ; Dang et al, 2017;Qian et al, 2014). Instead, aerosol direct effects are offset by reduced water vapor enabling increased shortwave downwelling and reduced surface albedo from BC is counteracted by substantial increases in cloud albedo.…”
Section: Discussionsupporting
confidence: 80%
“…For example, as R BC increases from 0.05 to 0.25 μm, the snow albedo reduction (integrated through the solar spectrum) decreases by 0.006 and 0.032 (absolute values) for 100 ppb BC in fresh ( R v = 100 μm) and aged ( R v = 1,000 μm) snow, respectively, averaged over different snow grain shapes. This leads to reductions of about 1.2 (0.54) and 6.4 (2.9) W m −2 in springtime BC‐snow albedo radiative forcing for fresh and aged snow, respectively, over the northern midlatitude (Arctic) snowpack, where the monthly all‐sky downward surface solar radiation is ~200 (~90) W m −2 in spring (Dang et al, ). This suggests that previous modeling studies using typical atmospheric BC sizes ( R BC ≤ 0.1 μm) have likely overestimated BC contamination effects on snow albedo, and the observed shift to larger BC sizes in snow could averagely reduce BC‐snow albedo forcing by ~40% or more for BC‐snow internal mixing under different BC and snow conditions.…”
Section: Climatic Implicationsmentioning
confidence: 99%
“…Therefore, the snow spectral albedo derived from satellite remote sensing in the VIS wavelengths can be used to estimate the impact of LAPs on snow albedo, which furthermore provides valuable information for modeling simulations to reduce relative uncertainties. To estimate the influence of mineral dust on snow albedo in the European Alps, Di Mauro et al (2015) defined a new spectral index, the snow darkening index, based on in situ measured snow spectral reflectance and Landsat 8 Operational Land Imager (OLI) data; they found that the snow darkening index could effectively track the content of mineral dust in snow. In addition, Di Mauro et al (2017) characterized the impact of LAPs on ice and snow albedo of the Morteratsch Glacier, a large-valley glacier in the Swiss Alps, using satellite (EO-1 Hyperion) hyperspectral data.…”
Section: Introductionmentioning
confidence: 99%